Method of use of biotechnological research (for example, biologically active substances of higher aquatic plants) in teaching Biology (Journal of Educational Sciences, 2018)
The article gives an opportunity for students to practice theoretical knowledge obtained by integratingbiotechnological research into methods of teaching biology in higher education institutions. With thehelp of biotechnological research, methods for conducting standard laboratory studies of pedagogical biologyin higher educational institutions are proposed. Laboratory classes are conducted efficiently, usingcomprehensive technological methods, depending on the pedagogical skills of the teacher. Based on theuse of biotechnological research, biologically active substances from high-water plants were determined.The subject of the study were aquatic plants Eichhornia crassipes, Pistia stratiotes, grown in a specialliquid medium, under the conditions of luministate. The amounts of biologically active substances fromaboveground and underground parts of aquatic plants were analyzed. Most of the biologically activeISSN 2520-2634 Journal of Educational Sciences. №2 (55). 2018 67Ерназарова Г.И. және т.б.substances are alkaloids, amino acids, anthraquinones, proteins, carbohydrates, coumarins,, polysaccharides,steroids, terpenes, phenolic acids and flavonoids. Methodical work is important in determiningthe method of detecting biologically active substances in special experimental work and analyzing theresults obtained by developing research abilities of students.Key words: Eichhornia crassipes, Pistia stratiotes aquatic plants, biologically active substances.